2010
DOI: 10.2298/fuace1002155j
|View full text |Cite
|
Sign up to set email alerts
|

Frost resistance of concrete with crushed brick as aggregate

Abstract: The investigation included concrete made by using recycled brick as aggregate. Experimental work included several types of concrete made with the same cement content (385 kg/m3), and same consistency (slump about 1 cm). Recycled brick and combination of natural river aggregate and recycled brick were used as aggregates. The influence of percentage and grain size of crushed brick aggregate on concrete compressive strength, water absorption and frost resistance were observed. On the basis of the results obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Internationally, the short number of papers published on the effect of recycled aggregate on freeze-thaw resistance have addressed: construction and demolition waste (C&DW) (Abbas et al, 2009;Salem et al, 2003); marble (Gencel et al, 2012); tyres (Richardson et al, 2012) and ceramic materials (Jankovic et al, 2010). The present study pioneers research on the resistance to this action in recycled concrete containing sanitary ware industry waste, an area unexplored to date.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Internationally, the short number of papers published on the effect of recycled aggregate on freeze-thaw resistance have addressed: construction and demolition waste (C&DW) (Abbas et al, 2009;Salem et al, 2003); marble (Gencel et al, 2012); tyres (Richardson et al, 2012) and ceramic materials (Jankovic et al, 2010). The present study pioneers research on the resistance to this action in recycled concrete containing sanitary ware industry waste, an area unexplored to date.…”
Section: Introductionmentioning
confidence: 86%
“…Other studies, however, showed a decline in bearing strength in concrete containing C&DW (Zhu and Li, 2009;Zaharieva et al, 2004) or clay-based roof tile or block waste (Jankovic et al, 2010;Topcu and Canbaz, 2007) as aggregate after exposure to freezethaw cycles. This discrepancy in the results can be attributed on the one hand to the compositional variability in C&DW and on the other to the effect of their quality and some of their physical properties (water absorption and fragmentation resistance) on their freeze-thaw resistance (Kevern et al, 2010).…”
Section: Scaling Surfacementioning
confidence: 95%
“…e assessment of pozzolanic activity is typically based on a strength activity index specified by ASTM C618, which limits the sum of silicon, ferric, and aluminium oxides to be at least 70% for pozzolans [23]. Plenty of studies have shown that those oxides of CBP were beyond 70% and exhibit high pozzolanic activity [ 20,21,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. As shown in Table 1, the sum of silicon, ferric, and aluminium oxide of CBP exceeded 70%, which proved that CBP had high pozzolanic activity; these components will promote the formation of C-S-H (calcium silicate hydrates) or C-A-H (calcium aluminate hydrates) and thus affected the performance of mortar and concrete.…”
Section: Pozzolanic Activity Of Cbpmentioning
confidence: 99%
“…Based on their experimental evidence, it can be stated that completely replacing the fine and coarse aggregate with RA reduces the dry unit weight of concrete masonry units by up to 25% [ 18 ]. Similarly, many other works demonstrate the impact of RBA on the characteristics of concrete (e.g., [ 19 , 20 , 21 ]). The impact of the limiting factors mentioned above on the final properties of concrete has also been researched.…”
Section: Introductionmentioning
confidence: 65%